Corelational Personality: Openness, Conscientiousness, Extraversion, Agreeableness, Neuroticism) and Intention to Act With Responsibility Environmental Behaviour - Zairin, Zairin (IJEEM - Indonesian Journal of Environmental Education and Management, 2017)
The objective of the research is to study the relationship personality (openness, conscientiousness, extraversion, agreeableness, neuroticism) and Intention to act with responsibility environment behaviour. It was a quantitative research with an study corelational methode conducted in Thariq bin Ziyad high school in Bekasi in 2015. The data were collected through questioner. The data analysis and interpretation indicate that 1. There is a positive relationship between personality with responsible environmental behavior. 2. There is a positive relationship between personality with the intention to act. 3. There is a positive relationship between personality, openness with the intention to act. 4. There is a positive relationship between personality, conscientiousness with intention to act. 5. There is a positive relationship between personality, extraversion with the intention to act. 6. There is a positive relationship between personality, agreeableness with the intention to act. 7. There is a positive relationship between personality, neuroticism with the Intention to act. 8. There is a positive relationship between the intention to act with responsible environmental behavior.